Evaluation of greenhouse gas emissions from landfills in the St. Petersburg area : utilization of methane in energy production, Metgas - Lappalainen, Sami; Kouvo, Petri (Publication / Lappeenranta University of Technology, Northern Dimension Research Centre, ISSN 1459-6679, 2004)
Tiivistelmä.
Keywords: energialähteet; energiantuotanto; hyötykäyttö; jätehuolto; kaatopaikat; kasvihuonekaasut; metaani; päästöt; ympäristötalous; energikällor; energiproduktion (industri); nyttobruk; avfallshantering; avstjälpningsplatser; växthusgaser; metan; utsläpp; miljöekonomi (ekonomi); Pietari; Venäjä; S:t Petersburg; Ryssland